2022
DOI: 10.3390/ijerph191811811
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Chinese Frailty Screening Scale: A Study among Community-Dwelling Older Adults in Shanghai

Abstract: Background: Based on intrinsic capacity (IC) as defined by the World Health Organization, an accelerated decline may be an important precursor of frailty among older adults; however, there is a lack of validated instruments that both screen for frailty and monitor IC. This study aims to develop a comprehensive and acculturative frailty screening scale to determine healthy aging among older Chinese adults. Setting and participants: A cross-sectional and a cohort study both based on community-dwelling older adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Frailty was measured by the Chinese Frailty Screening scale (CFSS), which includes 10 items that are scored on 0 (no) and 1 (yes). The total score ranged from 0 to 10, with a higher score indicating greater severity of frailty [25]. The internal consistency of the CFSS-10 in the present study showed good (Cronbach's α = 0.689).…”
Section: Frailtymentioning
confidence: 51%
“…Frailty was measured by the Chinese Frailty Screening scale (CFSS), which includes 10 items that are scored on 0 (no) and 1 (yes). The total score ranged from 0 to 10, with a higher score indicating greater severity of frailty [25]. The internal consistency of the CFSS-10 in the present study showed good (Cronbach's α = 0.689).…”
Section: Frailtymentioning
confidence: 51%
“…However, there is no standard assessment instrument. The most widely used measures are the FP (16) and the frailty index (FI), but these cannot be easily implemented in large-scale population studies or busy clinics (17). To assess frailty in large populations, it is important to find short-term rapid instruments that give reliable results for the risk of a negative event and to stratify older adults according to their level of frailty.…”
Section: Common Global Frailty Screening Toolsmentioning
confidence: 99%
“…Japan (80,81) China (17,20,82,83) Singapore (84,85) Denmark (86) Greek (38) African (87) Thai (15,88) Korean (39,89)…”
Section: Nephrologymentioning
confidence: 99%